THE EFFECTIVENESS OF VIDEO ON THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT EIGHT GRADE OF SMP GKPS 3 PEMATANGSIANTAR - NOMI SILVIA PURBA; HELFRIDA PURBA; SISKA FEBRINA GIRSANG; DEWI ANGRENI NATASIA SINAGA; SELVIANA NAPITUPULU (CV KULTURA DIGITAL MEDIA, 2022)
This research intends to find out the effectiveness of Video on students' ability in writing descriptive text at eight grade of SMP GKPS 3 Pematangsiantar. This research was designed as a quantitative method with quasi experimental research design. The data was taken from two class as the participants with a total of 60 students. Thirty students of VIII A and also thirty students of VIII B. The experimental class was treated using Video while control class was not treated using Video. The data were obtained by using pretest, treatment, and posttest. The pretest was held to know the students` basic ability or score before treatment was given. Meanwhile, the posttest was held to know the students` achievement and the significant effect the students' were taught through Video. The score of t-test (2,38) is higher than table (2,002) at the level of significance 5% for two tailed test, so Null Hypothesis is rejected and Alternative Hypothesis is accepted. Finally, by knowing the result, it is better if English teacher Using the Video media to improve the students' ability in writing descriptive text.